2020
DOI: 10.1093/aob/mcaa047
|View full text |Cite
|
Sign up to set email alerts
|

The role of lateral and vertical herkogamy in the divergence of the blue- and red-flowered lineages of Lysimachia arvensis

Abstract: Background and Aims Herkogamy, or anther–stigma separation, is known to reduce self-pollen deposition, but little is known about the relative efficacy of different modes or conformations of herkogamy. We assessed the effectiveness of vertical versus lateral herkogamy in preventing or promoting self-pollen deposition in the annual herb Lysimachia arvensis, a plant with lineages that differ in flower colour, and in which flowers first display lateral and then vertical herkogamy. Because mating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Genetic differentiation between color morphs strongly suggests that gene flow between them is restricted, being to some extent reproductively isolated. This is also supported by other results found in previous studies and in other previous papers: niche differentiation with the blue-flowered plants more adapted to dry habitats (Arista et al, 2013), differences in flowering phenology found here and in a previous study (Arista et al, 2013) that hinder pollen flow between morphs at least partially, pollinator visitation in polymorphic populations where bees show floral constancy and prefer blue-flowered plants (Ortiz et al, 2015;Jiménez-López et al, 2020a), differences in inbreeding depression and mating system (in this study), and the low frequency of intermediate phenotypes in polymorphic populations (Jiménez-López et al, 2019a;2020b). These facts clearly indicate a history of gene flow limitation between morphs, suggesting they are different lineages.…”
Section: Discussionsupporting
confidence: 78%
“…Genetic differentiation between color morphs strongly suggests that gene flow between them is restricted, being to some extent reproductively isolated. This is also supported by other results found in previous studies and in other previous papers: niche differentiation with the blue-flowered plants more adapted to dry habitats (Arista et al, 2013), differences in flowering phenology found here and in a previous study (Arista et al, 2013) that hinder pollen flow between morphs at least partially, pollinator visitation in polymorphic populations where bees show floral constancy and prefer blue-flowered plants (Ortiz et al, 2015;Jiménez-López et al, 2020a), differences in inbreeding depression and mating system (in this study), and the low frequency of intermediate phenotypes in polymorphic populations (Jiménez-López et al, 2019a;2020b). These facts clearly indicate a history of gene flow limitation between morphs, suggesting they are different lineages.…”
Section: Discussionsupporting
confidence: 78%
“…(Figure 4A and B), the blue-flowered form is better adapted to xeric conditions than the red-flowered form, which accounts for its high frequency in the Mediterranean region compared to the red form (Ortiz et al 2015). A difference in herkogamy between these morphs was recently described, blue flowers showing approach herkogamy while red flowers showed reverse herkogamy, with an effect on pollen deposition (Jiménez-López et al 2020). Colour polymorphism is frequent in species with deceptive pollination, and this may be due to disruptive selection caused by inaccurate discrimination by pollinators (Kagawa and Takimono 2016).…”
Section: Changing Colour In Spacementioning
confidence: 77%
“…The blue petals of L. arvensis contain malvidin derivatives, whereas orange petals contain pelargonidin derivatives ( Lawrence et al, 1939 ; Harborne, 1968 ; Ishikura, 1981 ). Although both L. arvensis flower colors have long been described as different morphs, recent molecular phylogenetic studies indicate that these flower color phenotypes reflect very closely related, yet distinct, evolutionary lineages ( Jiménez-López, 2019 ; Jiménez-López et al, in review ) with some degree of reproductive isolation ( Jiménez-López et al, 2020 ). Pollinators (mainly Halictus spp.…”
Section: Introductionmentioning
confidence: 99%